No association between systemic sclerosis and C77G polymorphism in the human PTPRC (CD45) gene - Kirsten, Holger; Blume, Mechthild; Emmrich, Frank; Hunzelmann, Nico; Mierau, Rudolf; Rzepka, Rita; Vaith, Peter; Witte, Torsten; Melchers, Inga; Ahnert, Peter (The Journal of rheumatology, 2008)
OBJECTIVE The functional variant C77G (rs17612648) of PTPRC (CD45) was described to confer risk for systemic sclerosis (SSc) in German Caucasians. We analyzed this association in an independent, larger German cohort. METHODS We genotyped 171 cases and 179 controls. Cases were subgrouped according to sex, autoantibody profiles, or clinical subsets. RESULTS No association of SSc with C77G was detected in the whole dataset, in subgroups, or in combined analyses with a previous study. CONCLUSION The results do not confirm PTPRC C77G as a general and independent risk factor for development of SSc.